KONSEP BERBANGSA DAN BERNEGARA PERSPEKTIF K.H. MAIMOEN ZUBAIR DAN RELEVANSINYA PADA PENDIDIKAN ISLAM MODERAT DI INDONESIA - Saeful Anam; Aan Abuel Hasan (Atthiflah: Journal of Early Childhood Islamic Education, 2022)
This article explains the Concept of Nation and Statehood K.H. Maimoen Zubair's Perspective and Its Relevance to Moderate Islamic Education in Indonesia. We know that Indonesia is not an Islamic country, but is favored by many non-Muslims. Like the Messenger of Allah SAW. He was Muslim but his birth was favored by Abu Lahab. So upholding the Indonesian nation is a must. K.H. Maimoen Zubair captured these differences as part of the concept of nation and state. And that distinction should not be exaggerated so that the Indonesian people can live in harmony. This type of research is qualitative research with a literature review approach. The data used is to collect various reference sources related to K.H. Maimoen Zubair either in book data or some audio data in the form of his lectures on social media. The results of this study show that K.H. Maimoen Zubair asserts that nature must change and every change inevitably leaves a precedent. Mustasyar PBNU also invites Kudus students to learn the history of the Glory of Brawijaya whose power not only covers Java but also outside Java during the period of da'wah Sunan Ampel. This is part of K.H. Maimoen Zubair's efforts to instill a sense of love for the motherland; love for the nation and the country into the students. In the past, K.H. Maimoen Zubair said that the Arabs who came to Irian called it Irian with the name Uryan which means naked. The progress made by the Arabs at that time was not as fast as that of Java, whose Islam was brought by Wali Songo. The good relationship between Majapahit and Cambodian Islam which is famous for Campa then gave birth to the figure of the cleric plus king, namely Raden Patah and other major Islamic figures.